Virtual Lactation Support for Breastfeeding Mothers During the Early Postpartum Period - Jordan, Shakeema (My University, 2021)
Breastmilk is the clinical gold standard for infant feeding and nutrition. Although maternal and child health benefits are associated with breastfeeding, national, state, and local rates remain below target. In fact, 60% of mothers do not breastfeed for as long as intended. During the early postpartum period, mothers cease breastfeeding earlier than planned due to common barriers such as lack of suckling, nipple rejection, painful breast or nipples, latching or positioning difficulties, and nursing demands. Providers in the outpatient setting are significant resources to increase breastfeeding duration, eliminate common barriers, and improve breastfeeding practices. This paper discusses the implementation of virtual lactation support for breastfeeding mothers and families within an outpatient pediatric setting to reduce early cessation among breastfeeding mothers within the first four-week postpartum period.
Keywords: breastmilk, breastfeeding, lactation, four-week postpartum, virtual, support